Polymorphism in p-aminobenzoic acid. Issue 13 (22nd January 2019) - Cruz-Cabeza, Aurora J.; Davey, Roger J.; Oswald, Iain D. H.; Ward, Martin R.; Sugden, Isaac J.
Abstract : We review the polymorphism of p -aminobenzoic acid ( p ABA), a model drug compound whose crystallisation and polymorphic behaviour has been extensively studied in recent years. Abstract : We review the polymorphism of p -aminobenzoic acid ( p ABA), a model drug compound whose crystallisation and polymorphic behaviour has been extensively studied in recent years. Beyond the well-known and characterised α and β forms, p ABA also crystallises as a γ polymorph, which is structurally similar to the α form. In addition we also compare the newly reported δ form, obtained by high pressure crystallisation and through compression of the α-form. A structural analysis and comparison of all of the forms is presented, the conditions by which each of them is obtained summarised. Crystal structure prediction calculations have also been carried out in order to probe the solid form energy landscape of this compound. The overall picture of the polymorphism of p ABA, reveals, surprisingly, the rarity of the β form.